Analysis of mode II strain energy release rates in end-notched flexure tests of carbon fiber-reinforced plastic curved beams. (1st February 2022) - Sako, Ryota; Aoki, Ryoma; Higuchi, Ryo; Ueda, Masahito; Urushiyama, Yuta; Yokozeki, Tomohiro
Graphical abstract: Highlights: Theoretical equations for curved beams of ENF tests are formulated. Verifications of compliance and strain energy release rate with 2-D FEM show good agreements. Abstract: The present study aims to formulate strain energy release rates (SERR) for curved beams, which are supposed to be cut from tanks or cylinders, in End-Notched Flexure (ENF) tests based on Euler-Bernoulli's and Timoshenko's curved beam theories. The derived SERRs based on the curved beam theories were compared with those based on the flat beam theory for specimens with various geometries to prove the validity of using the curved beam theory in the ENF tests of curved beams. The validity of the derived compliance and SERRs was verified for the specimens with various geometries using a two-dimensional finite element analysis, in which virtual crack closure techniques were used to calculate the SERRs. The results revealed that Euler–Bernoulli's curved beam theory was effective in cases with large radius-of-curvature-to-thickness ( R / h ) values but not in those with small R / h values, whereas Timoshenko's curved beam theory was effective even for small R / h values.